Dual-Responsive Supramolecular Chiral Assemblies from Amphiphilic Dendronized Tetraphenylethylenes - Jianan Zhang; Xueting Lu; Wen Li; Afang Zhang (Molecules, 2023)
Supramolecular assembly of amphiphilic molecules in aqueous solutions to form stimuli-responsive entities is attractive for developing intelligent supramolecular materials for bioapplications. Here we report on the supramolecular chiral assembly of amphiphilic dendronized tetraphenylethylenes (TPEs) in aqueous solutions. Hydrophobic TPE moieties were connected to the hydrophilic three-fold dendritic oligoethylene glycols (OEGs) through a tripeptide proline–hydroxyproline–glycol (POG) to afford the characteristic topological structural effects of dendritic OEGs and the peptide linker. Both ethoxyl- and methoxyl-terminated dendritic OEGs were used to modulate the overall hydrophilicity of the dendronized TPEs. Their supramolecular aggregates exhibited thermoresponsive behavior that originated from the dehydration and collapse of the dendritic OEGs, and their cloud point temperatures (Tcps) were tailored by solution pH conditions. Furthermore, aggregation-induced fluorescent emission (AIE) from TPE moieties was used as an indicator to follow the assembly, which was reversibly tuned by temperature variation at different pH conditions. Supramolecular assemblies from these dendronized amphiphiles exhibited enhanced supramolecular chirality, which was dominated mainly by the interaction balance between TPE with dendritic OEG and TPE with POG moieties and was modulated through different solvation by changing solution temperature or pH conditions. More interestingly, ethoxyl-terminated dendritic OEG provided a much stronger shielding effect than its methoxyl-terminated counterpart to prevent amino groups within the peptide from protonation, even in strong acidic conditions, resulting in different responsive behavior to the solution temperature and pH conditions for these supramolecular aggregates.